Costs and Outcomes in Children's Social Care : Messages from Research. - Beecham, Jennifer (Jessica Kingsley Publishers, 2006)
Care services for children depend on a limited supply of resources; it is vital that these are used to best effect. This book considers the efficiency and cost-effectiveness of these services and their contribution to children's well-being. The book presents the findings of a set of original research studies. It looks at services provided by the statutory, for-profit and voluntary sectors, examining the way they are delivered and how resources are distributed. It examines the cost of providing particular services, the extent to which they improve outcomes for children and the degree to which t.